Drunkorexia: An investigation of symptomatology and early maladaptive schemas within a female, young adult Australian population. (14th May 2020) - Powell‐Jones, Alycia; Simpson, Susan
Abstract: Objective: Drunkorexia is a trend on the rise within the young adult population with significant physical, psychological, and social health implications. Many studies have investigated the link between Early Maladaptive Schemas (EMS) and both eating disorders and substance misuse. To date, no studies have specifically focused on EMS amongst those with Drunkorexia behaviours. The main objectives of this study were to further investigate the prevalence of Drunkorexia behaviour amongst Australian young adult females, and to elucidate the pattern of EMS and behaviours associated with Drunkorexia amongst young adult female Australian students. Methods: This study used a cross‐sectional, between groups, correlational design. Participants were Australian university students, aged 18–24 years old. Results: In excess of 28% participants reported engaging in characteristic Drunkorexic behaviours to specifically offset ingested alcohol calories while not engaging in such behaviours routinely for any other reason or with any other type of food or drink. The EMS most predictive of Drunkorexia‐type behaviour were Insufficient Self‐Control, Emotional Deprivation, and Social Isolation. EMS significantly contributed to the variance in Drunkorexia‐type behaviours, over and above that explained by eating disorder and binge drinking symptomatology. Conclusions: Increasing numbers of individuals are endorsing symptoms of Drunkorexia‐type behaviour, increasing the risk of potential physical, psychological, and social health‐related problems. Addressing key EMS that may be associated with Drunkorexia‐type behaviours may strengthen future preventative and intervention programs. Given the exploratory nature of this research, further studies are required to clarify the relationship between EMS and Drunkorexia.